Computerizing Tax and Customs Administrations - Engelschalk, Michael; Melhem, Samia; Weist, Dana (World Bank, Washington, DC, 2012)
Computerization is an important part of World Bank tax and customs projects. Revenue administration computerization projects should be seen in the broader context of public sector reforms. They touch on issues such as the government's overall strategy for information technology, the revenue agency's autonomy in maintaining information technology systems, civil service laws and procurement policies, and communication and cooperation among government agencies. Drawing on completed and ongoing projects -- especially the Philippines Tax Computerization Project -- this note offers recommendations for project design and implementation.